Legal Burden of Obligation to Pay Tax on Business Results in the Zakat Concept - Harahap, Budi (PT. Riset Press International, 2023)
This research is the understanding of the people who are aware of the law in paying zakat from the business. The focus of this research is how the understanding of the law-conscious community in paying zakat from business results. Furthermore, this type of research is field research (direct research on objects or subjects in the field to obtain data). The results of this study are to examine people's understanding of paying zakat from the business. Zakat is worship in the field of property, which relates to people who give zakat ( muzakki ), recipients ( mustahik ), assets issued by zakat, and society as a whole. Islam has a concept of zakat which is a concern for the weak. Zakat is paid by a muzakki given to the mustahik. In this study, it appears that the understanding of people of Lengayang District only understands the zakat fitrah that they pay during the fasting month. For the measure of payment, they only estimate it. In the efforts that must be made so that people's understanding of the obligation of zakat can be achieved through coaching muzakki and mustahiq, of course, there is good cooperation between all parties involved, namely the community itself, the Zakat Collection Unit, village officials, religious scholars, and religious extension workers are no exception.